Effects of Various Steam Flooding Injection Patterns and Steam Quality to Recovery Factor - Kusumastuti, Indri; Erfando, Tomi; Hidayat, Fiki (Pekanbaru Riau: Program Studi Teknik Perminyakan FT Universitas Islam Riau, 2019)
The main principle of steam flooding is to reduce the oil viscosity using hot steam that is injected into the reservoir. In the field implementation there are several injection patterns that can be applied for steam flooding. This research aims to determine the effect of several injection patterns and steam quality on oil recovery factor. Therefore, it can be known the injection pattern and steam quality are right to obtain the best recovery factor. Analysis was carried out on injection patterns including five-spots, inverted five-spots, seven-spots, inverted seven-spots, nine-spots, and inverted nine-spots. The variations in the steam quality used are 50%, 70% and 90%. The simulation model a 3-dimensional cartesian with grid block size 5x5x5 on CMG STARS. The parameters in this steam flooding scenario are temperature at 450° F, injection pressure of 500 psi, and injection rate of 1000 bbl /day. Of all the scenarios tested the best results were in the inverted seven spot pattern with steam quality 0.9, where recovery factor was 35,1% and total cumulative production was 269397 bbl.